2012
DOI: 10.1002/etc.1787
|View full text |Cite
|
Sign up to set email alerts
|

In ovo exposure to nonylphenol and bisphenol A resulted in dose-independent feminization of male gonads in Japanese quail (Coturnix japonica) embryos

Abstract: Sex reversal effects of nonylphenol and bisphenol A on the gonads in F(1) (AWE × WE) Japanese quail (Coturnix japonica) embryos were investigated using an in vivo screening model developed previously. The F(1) (AWE × WE) Japanese quail are a useful avian model because sex differentiation is confirmed by the plumage color before hatching, ruled by a criss-cross inheritance. The nonylphenol at 200, 2,000, 20,000, and 200,000 ng/egg and bisphenol A at 20, 200, 2,000, and 20,000 ng/egg were injected into the egg w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Many natural and synthetic substances in the environment interfere with the physiological functions of humans and animals. In particular, endocrine-disrupting chemicals (EDCs) (Colborn et al, 1993) have attracted much interest because of their industrial and domestic applications versus Abbreviations: DSB, DNA double-strand break; EDC, endocrine-disrupting chemicals; GVBD, germinal vesicle breakdown; MI/II, metaphase I/II; MXC, methoxychlor; ROS, reactive oxygen species; SAC, spindle assembly checkpoint ß 2016 WILEY PERIODICALS, INC. their potential risks to animal health (Yang et al, 2006;Schug et al, 2011); indeed, EDCs affect sexual behaviors (Gray et al, 1989), fertility (Fowler et al, 2012), feminization (Oshima et al, 2012;Tian et al, 2012), and development of reproductive organs (Eroschenko et al, 1995). Recent studies demonstrated that EDCs also impact human health (Ho et al, 2012;Chauhan and Grissom, 2013;Faniband et al, 2014), directly interfering with steroid hormone-receptor binding and/or impacting cell signaling pathways (Henley and Korach, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many natural and synthetic substances in the environment interfere with the physiological functions of humans and animals. In particular, endocrine-disrupting chemicals (EDCs) (Colborn et al, 1993) have attracted much interest because of their industrial and domestic applications versus Abbreviations: DSB, DNA double-strand break; EDC, endocrine-disrupting chemicals; GVBD, germinal vesicle breakdown; MI/II, metaphase I/II; MXC, methoxychlor; ROS, reactive oxygen species; SAC, spindle assembly checkpoint ß 2016 WILEY PERIODICALS, INC. their potential risks to animal health (Yang et al, 2006;Schug et al, 2011); indeed, EDCs affect sexual behaviors (Gray et al, 1989), fertility (Fowler et al, 2012), feminization (Oshima et al, 2012;Tian et al, 2012), and development of reproductive organs (Eroschenko et al, 1995). Recent studies demonstrated that EDCs also impact human health (Ho et al, 2012;Chauhan and Grissom, 2013;Faniband et al, 2014), directly interfering with steroid hormone-receptor binding and/or impacting cell signaling pathways (Henley and Korach, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Over 2.7 million tonnes of BPA are produced globally each year and it is 1 of the most potent environmental estrogens based on a number of in vitro test systems . Bisphenol A induced Müllerian duct malformations in female bird embryos and feminization of male gonads in Japanese quail . Based on the estrogenic effects observed in avian species, the detection of BPA in liver tissue (0.94 ng/g wet wt) of a high‐trophic level avian species, the common cormorant ( Phalacrocorax carbo ) , is of concern.…”
Section: Introductionmentioning
confidence: 99%
“…From our pervious study, we found that in ovo exposure of phytoestrogen to male quail embryo caused thickening of the cortex of the left male gonad . The character of having thick cortex in male quail embryonic gonad after exposure to exogenous estrogens is called "ovotestis" (Perrin et al, 1995;Berg et al, 2001;Oshima et al, 2012). It has been reported that a number of ER in germinal epithelial cells were increased by phytoestrogen (Anderson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%